(untitled) (Studia Prawnicze / The Legal Studies, 1984)
The work has been based on the results of a few years’ studies conducted (starting from 1977) on the initiative of the Judicial Research Institute at the Ministry of Justice. Having taken into account cases in which courts in the statement of reasons expressed an opinion on the reliability of witnesses, statements may be divided into 2 groups: • statements based on data concerning the person of a witness: features of his character, manner of giving evidence, attitude towards the parties, etc. • statements based on the analysis of the deposition of the witness in the context of depositions of other witnesses and all the evidence in the case. The research showed that only in relation to 190/0 of witnesses the reliability of their deposition was of a "subjective" character and in relation to the remaining 81% of witnesses — of an "objective" character. it means that only in relation to one witness to five, who the court trusts, the statement is based on characte¬ristic features of the witness, his possibility and ability to perceive, ,annex of behaviour, attitude towards the parties, etc. The situation is different in case of "rejection" of deposition of a witness because of his here the statement of reasons the court takes into account just that type of personal data on the witness. However, courts’ attitude towards this problem is sometimes too formalistic and schematic and, in consequence, a witness is considered unreliable only be¬cause he is a relative of the accused or injured person. The research also showed that there is an unwritten rule (i.e. not included in the rules of procedure) accor¬ding to which witnesses summoned by the court ex officio and on the motion of a public prosecutor are considered more reliable than witnesses summoned on the motion of the accused and a private prosecutor. The above mentioned interviews showed that every third respondent admitted that a criminal record of the witness directly influences the final evaluation of deposition, and others said that this factor may indirectly influence the evaluation of evidence because they are more critical towards those witnesses. Public prosecutors, in the majority of cases, said that a criminal record of the witness influences the evaluation of his deposition by the court. Statistically, men, as compared with women, attach less importance to that factor.